PESANTREN DALAM HIMPITAN ARUS GLOBALISASI DAN RADIKALISME AGAMA - Jamal Ghofir (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2019)
Pesantren is a stronghold of Indonesian morality. Pesantren never teach intolerance, coercion of religion, judge fellow human beings and even fellow Muslims. And pesantren never teach radical values ​​in every learning to students. He was present as part of the formation of Indonesian civilization. Therefore, the existence of pesantren becomes very important in the continued development of the values ​​of Islamic teachings which are rahmatan lil alamin and the stronghold of the strength of Indonesian morality. But lately, the existence of pesantren is confronted by various challenges of the times. The current position of globalization and the openness of democracy are part of the struggle for the challenges of the times and the seeds of religious radicalism develop behind the openness of democracy. Therefore, strengthening the existence and position of Islamic boarding schools must and always be strengthened both in the realm of the learning system and in its development. Thus, the existence of Pesantren will continue to exist as a stronghold of the strength of the morality of the Indonesian nation, which spread friendly and friendly without having to be burdened with the current of globalization and the progress of the times.